Does location matter? STI and DUI innovation modes in different geographic settings. (January 2023) - Doloreux, David; Shearmur, Richard
Abstract: Since Jensen et al.'s (2007) seminal paper conceptualizing innovation modes, many empirical studies have demonstrated the validity of the concept. There have recently been two developments that may help clarify our understanding of innovation modes. First, innovation modes are being sub-divided between those internal and those external to the firm. Second, it is increasingly suggested that the connection between innovation mode and innovation outcome may be context dependent, with specific interest in regional context. In this paper we contribute to this debate by examining whether the connection between internal and external innovation modes and innovation outcomes varies across two types of context: geographic (with establishments classified according to their distance from a metropolitan area) and technological (in order to position our geographic results). We show that for some types of innovation and for some types of mode, geographic context is a determining factor, whereas technological context has no effect on the relationship. Highlights: We study how the connection between innovation modes and innovation outcomes varies across different geographical contexts. The study is based on original firm-level data in the province of Québec. The analysis reveals that for some types of innovation and for some types of mode, geographic context is a determining factor, whereas technological context has no effect on the relationship. Metropolitan-periphery dimension can play a role in understanding the connection between innovation mode and innovation outcome.